PELATIHAN JURNAL UMUM PERUSAHAAN JASA KEPADA SISWA SMAN 2 JAKARTA - Angela, Karin Novena; Adang, Ferry (Jurnal Serina Abdimas, 2024)
The Service Company General Journal Training at SMAN 2 Jakarta was designed with the aim of providing opportunities for students who are interested in the world of education to act as teacher assistants at school. The main focus of this training is to provide understanding and application of General Journals in recording service company transactions. Through this training, students are invited to be directly involved in recording service company business accounting activities along with the necessary explanations through diaries and related documentation. It aims to provide students with direct experience and real practice in the world of service company accounting. Teaching Assistance at SMAN 2 Jakarta is carried out for approximately 3 months. The methods used in Teaching Assistance are discussion, conventional and question and answer methods. The discussion method is used when giving practice questions to students in groups where students can discuss with their friends and when students have difficulty working, students can ask the author. Conventional methods are used to explain material on a whiteboard or by using a projector. The question and answer method is carried out with students by asking questions when they have finished explaining the material. This training has had a positive impact at the secondary education level, especially at SMAN 2 Jakarta. By involving students in the role of teacher assistants, this training indirectly helps in creating an interactive learning atmosphere. It is hoped that this training can provide a positive boost to students' interest in accounting and business, as well as provide a sustainable contribution to curriculum development at SMAN 2 Jakarta.